Wool appliqué heirlooms : 15 antique-inspired projects & techniques - Blythe, Mary A., 1968- (C&T Publishing, 2019)
Enjoy quiet time with time-honored wool appliqué! Add warmth and texture to your home with wool appliqué. Sewing in the popular folk-art style, you'll stitch fifteen projects, including thirteen heirloom-worthy table mats and two versions of an Advent calendar. Learn how reverse appliqué brings depth and color to your handwork without the bulk of additional layers. This guide offers advice on choosing and using wool (even scraps!), plus valuable techniques and tips for wool hand stitchers.<U+2022> Make heirlooms your family will treasure <U+2022> Be inspired by beautiful styled photos with seasonal theme <U+2022> Choose the best tools and get advice on stitches